2017
DOI: 10.7717/peerj.2835
|View full text |Cite
|
Sign up to set email alerts
|

Vascular plant biodiversity of the lower Coppermine River valley and vicinity (Nunavut, Canada): an annotated checklist of an Arctic flora

Abstract: The Coppermine River in western Nunavut is one of Canada’s great Arctic rivers, yet its vascular plant flora is poorly known. Here, we report the results of a floristic inventory of the lower Coppermine River valley and vicinity, including Kugluk (Bloody Falls) Territorial Park and the hamlet of Kugluktuk. The study area is approximately 1,200 km2, extending from the forest-tundra south of the treeline to the Arctic coast. Vascular plant floristic data are based on a review of all previous collections from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 184 publications
(1,317 reference statements)
4
37
0
Order By: Relevance
“…As such, our empirical data support the established relationship between vascular plant diversity and summer temperature, as other studies have demonstrated (e.g., Bay 1997). The relationship was not as strong, however, in a recent analysis of the well-documented mainland Arctic flora of the lower Coppermine River valley and vicinity (Saarela et al 2017).…”
Section: Comparison Of the Vascular Flora Of The Study Area And Othersupporting
confidence: 91%
See 2 more Smart Citations
“…As such, our empirical data support the established relationship between vascular plant diversity and summer temperature, as other studies have demonstrated (e.g., Bay 1997). The relationship was not as strong, however, in a recent analysis of the well-documented mainland Arctic flora of the lower Coppermine River valley and vicinity (Saarela et al 2017).…”
Section: Comparison Of the Vascular Flora Of The Study Area And Othersupporting
confidence: 91%
“…Overall, our results are consistent with other Arctic floristic studies that similarly demonstrated that total species diversity documented in an area increases with search effort through time, that different collectors at different times tend to document different subsets of total species diversity, and that in order to account for total vascular plant biodiversity in an area where there has been previous collecting, review of existing collections in multiple herbaria, the literature and newly collected material is necessary (Saarela et al 2013a, Saarela et al 2017, Saarela et al 2020.…”
Section: Different Collectors Gathered Different Subsets Of Taxa In Tsupporting
confidence: 90%
See 1 more Smart Citation
“…The QPT catchment is 14.5 km 2 with a modern vegetation cover of dwarf‐shrub tundra dominated by Betula glandulosa (here considered synonymous with B. nana spp. exilis after Saarela, Sokoloff, & Bull, ), Salix spp. (willow), other ericaceous shrubs, and sedges.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they allow the extension of many boreal species into the (sub-) Arctic as outlier populations (e.g. [15,16]). Through the maintenance of a wide range of microhabitats, the river valleys may be one of the key environments for preservation of biodiversity when the climate changes ([14,17]).…”
Section: Introductionmentioning
confidence: 99%